Analisis Pembelajaran Berdiferensiasi Pada Pelaksanaan Praktik Pengalaman Lapangan (PPL) Pendidikan Profesi Guru (PPG) Dalam Upaya Penerapan Kurikulum Merdeka Pada Kelas 4 SD Negeri Gayamsari 02 - Eka Pujiastuti; Ida wijayanti; Qoriati Mushafanah (Journal on Education, 2024)
In social life there is a diversity of individuals, including in the world of education. Where each student has their own learning needs. A teacher must be able to accommodate students' learning needs so that learning can be achieved and run effectively. Differentiated learning is a solution to meet these varied learning needs. This research aims to implement the application of differentiated learning in Indonesian language subjects during Field Experience Practice. The research method used is qualitative with a case study approach. Data analysis was carried out through triangulation, namely by combining the results of observations, tests and documentation to verify the data. The research was conducted in class 4A, totaling 24 students at SDN Gayamsari 02 Semarang. Teachers make initial preparations by carrying out cognitive diagnostic tests to see students' basic knowledge abilities and based on data when carrying out Field Experience Practice 1 last November 2023. Then develop appropriate learning strategies. One of the obstacles experienced by researchers is the differentiation of understanding learning. Where researchers only use the differentiation process, while content and product differentiation is not implemented. The research results show that learning can run well even though the results obtained are not significant.